G218 The contribution and impact of specialist and advanced children's nursing practice to contemporary health care. (27th April 2015) - Gelder, C; Campbell, J; Clarke, D; Fairley, I; Flaherty, J; Hollis, R; Houston, A; Jagger, H; Krinks, K; Smith, F; Tulloh, R
Abstract : Aims: To demonstrate that children's nurses working at a specialist advanced and consultant level can make a significant impact and contribution to the redesign, development and delivery of effective services for children, young people (CYP) and their families. To develop a shared understanding of a flexible transparent career framework with commissioners, managers and nurses which enables advanced clinical practice and leads improved health outcomes for CYP. Methods: A group of expert children's nurses from a range of disciplines and specialisms collaborated to review national and professional policy guidance to gain consensus regarding the incremental development of specialist and advanced careers which are sustainable, add value and contribute to new interdisciplinary ways of working. Real life nursing roles and services exemplars were used to illustrate innovative developments. These ranged from child specific acute care alternatives to A&E through to nurse led rapid access clinics for the assessment and diagnosis of long term conditions such as diabetes and also to clinical academic research roles which enable reciprocal practice and research synergy. Results: The guidance document created recognises that health outcomes for CYP in the United Kingdom are in many ways subordinate to those in comparable European countries. This led to recognition of the need for a fundamental review of child health services, and modernisation of the workforce for future service provision. The importance of a flexible career framework which supports clinical and academic expertise developing in parallel has been highlighted as integral. The key attributes of specialist, advanced and consultant level practice are made transparent to support a planned approach to commissioning and developing services. Innovative exemplars highlighted potential for improved patient experience, reduced admission rates and length of stay. Advanced practitioners challenge existing practice and work autonomously, educate others and build a research and evidence led care environment. Conclusion: This important guidance document demonstrates that children's nurses working at advanced levels of practice across a range of healthcare settings can lead the way to achieving excellence in health care and health outcomes.